Aerobic exercise decreases interstitial glucose concentrations up to 2 h after exercise in dogs with insulin-treated diabetes mellitus: a preliminary study - Mampe, Jessica R.; Stefanovski, Darko; Hess, Rebecka S. (Frontiers in Veterinary Science, 2025)
IntroductionThe effect of aerobic exercise on glucose concentration has been reported in healthy normal and over-conditioned dogs and in experimental dog models. However, the effect of aerobic exercise on interstitial glucose concentration (IG) has not been reported in dogs with insulin-treated naturally-occurring diabetes mellitus.ObjectiveDetermine if aerobic exercise decreases IG in outpatient diabetic dogs.MethodsFive NPH insulin-treated client-owned diabetic dogs were prospectively enrolled into this interventional longitudinal cohort study. Dogs with a flash glucose monitoring system performed once daily aerobic exercise over 30 min for 7 consecutive days, if IG was ≥60 mg/dL during the preceding 12 h of observation. Dogs weighing <10 kg exercised (walked or jogged) for 1.5–2 miles, dogs 10–20 kg exercised for 2–2.5 miles, and dogs >20 kg exercised for 2.5–3 miles. Multivariable mixed-effects linear regression models followed by post-hoc analyses were used to estimate the marginal mean differences between IG 0.5, 1, 1.5, 2, and 4 h after exercise compared with marginal mean baseline IG measured twice over 30 min just before each daily exercise period, which served as the control.ResultsMarginal means (95% confidence intervals) of IG were significantly lower 1.5 h after exercise [188 mg/dL (96-281 mg/dL)] and 2 h after exercise [185 mg/dL (82–287 mg/dL)] compared with marginal mean IG measured just before exercise [223 mg/dL (129–317 mg/dL, p = 0.03, p = 0.008, respectively)]. Marginal means of IG were not significantly different 4 h after exercise compared with marginal mean IG measured just before exercise.ConclusionOur preliminary data suggest that aerobic exercise may reduce IG levels up to two hours following exercise. These findings indicate that exercise could potentially serve as an adjunct approach to managing insulin-treated diabetic dogs in a home setting.